Redefinition of Mesoleptobasis Sjöstedt 1918 with the inclusion of Metaleptobasis cyanolineata (Wasscher 1998) comb. nov. and description of a new species, Mesoleptobasis elongata (Odonata: Coenagrionidae) - Garrison, Rosser W.; Ellenrieder, Natalia Von (Zootaxa, 2009)
Metaleptobasis cyanolineata is transferred to Mesoleptobasis and a new species, Mesoleptobasis elongata, is described. The genus is diagnosed by the combination of rounded frons, highly modified pronotum with long processes at least in males, pterothoracic color pattern lacking dark mid-dorsal stripe, pretarsus with supplementary tooth vestigial or absent, vein descending from quadrangle forming an unbroken line to wing margin, and genital ligula with a small inner fold and with spine-like projections on lateral margins distal to flexure. Its species are illustrated, mapped, and keyed.